Research Methods for Business Students. - Saunders, Mark. (Pearson Education, Limited, 2023)
Support your students' research project with robust and pragmatic guidance on the entire process. Research Methods for Business Students introduces a range of features, including a glossary of terms, case studies and articles, and self-study prompts that will encourage your students to apply what they have learned to their own research project.